Intraoperative Use of Betadine Irrigation is Associated With a 9-Fold Increased Likelihood of Penile Prosthesis Infection: Results From a Retrospective Case-Control Study. Issue 3 (26th June 2020) - Manka, Madeleine G.; Yang, David; Andrews, Jack; Chalmers, Brian; Hebert, Kevin; Köhler, Tobias S.; Trost, Landon
Abstract: Introduction: Infection remains a persistent complication of penile prosthesis (PP) surgery. Despite popularity of Mulcahy's PP washout protocol, Betadine has known tissue toxicity. Aim: We evaluated PP infection rate based on the type of intraoperative irrigation used, ½ strength Betadine vs vancomycin/gentamicin. Methods: We reviewed a prospective database of men undergoing primary, revision, and salvage PPs. No other changes to operative or perioperative techniques occurred after the change in irrigation solution. Univariate and logistic regression analyses were used to evaluate differences in infection rate with use of Betadine vs vancomycin/gentamicin irrigation. Potential confounders were reviewed. Main Outcome Measure: The primary outcome was rate of PP infection before and after change of intraoperative irrigation. Results: From 2014 to 2018, 217 patients underwent PP placement at our institution by a single surgeon; of whom, 21 (9.7%) experienced an infection (primary = 10 [7.1%], revision = 11 [17.19%], salvage = 0 [0%]). Overall, 152 (70%) received irrigation with Betadine and 65 (30%) with Vancomycin/Gentamicin. Univariate analysis demonstrated significantly increased infection rates with Betadine irrigation (odds ratio [OR]: 4.64, P = .006) and with revision surgery (OR: 2.68, P = .02). Significance of increased infection rate with Betadine was maintained (OR: 9.3; P = .025) after controlling for age, body mass index, Charlson comorbidity index, smoking, diabetes, primary vs revision/salvage, prior penile surgery, use of ectopic reservoir, and adjunctive glanulopexy. Conclusions: Changing from intraoperative Betadine to vancomycin/gentamicin solution dramatically reduced infection rates among men undergoing PP placement in both primary and revision cases. We hypothesize that differences in infection rate may relate to the relative toxicity or non-sterile nature of Betadine. Manka MG, Yang D, Andrews J, et al. Intraoperative Use of Betadine Irrigation is Associated With a 9-Fold Increased Likelihood of Penile Prosthesis Infection: Results From a Retrospective Case-Control Study. Sex Med 2020;8:422–427.